Answer:
6
Step-by-step explanation:
(-1^2 + -1-2) / (2*-1^2 + -2-3)
1 + -3 / 2 + -5
-2 / -3
= 6
The profit that John got from the last 50 was $5000.
10 cuz it’s a 2 € 10 and it’s 10
The answer: 0, 4/5 and 5
Explanation: first, we factor out 2x and get: 2x(5x^2-29x+20)=0
In order for this equation to be equal to zero, either 2x must equal to zero or (5x^2-29x+20) must equal to zero
Having said that, if:
2x = 0
X=0
If:
(5x^2-29x+20) = 0
X=4/6, x=5
Answer:
The second and the last options.
Step-by-step explanation:
15/ 2/9 =67.5 Solve the original problem
15*2/9 =3.33333333333
15*9/2 =67.5
(15* 1/9) /2=0.833333333333333
15*9* 1/2 =67.5